Mutagenic effect of hydroxyl amine on resistance of antibiotics and heavy metals in isolation of Klebsiella pneumoniae - Ibrahem Talal Dawood; Khaled Daham Ahmed (College of Education for Pure Sciences, 2009)
Abstract Twenty isolates of bacteria Klebsiella were collected from different clinical specimens of human infection from Al-Salam, Al-Khansa'a and Ibn-Alatheer hospitals in Mosul city. These isolates were identified by using microscopical examination, culture characteristics, biochemical tests and API20E test used for confirmation detection. The isolates belonged to the species K. pneumonia. The ability of the isolates to resist nine antibiotics and heavy metals (cadmium chloride and mercury chloride) were tested. The isolates varied in there antibiotic resistance, but they all they resisted heavy metals. Moreover the mutagen hydroxylamine (H.A.) was used to remove the antibiotic and heavy metal resistance in these isolates by two methods. 1M concentration of (H.A.) for 50 minutes treatment appear to be very effective and high percents of antibiotic resistance for amoxicillin 40% and trimethprim 38% occur in some isolates and for cefalixin 28% in other isolates. Increasing the mutagen concentration to 2M for 50 minutes appeared even more effective.